2020
DOI: 10.17352/2455-5479.000068
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing health facility-based data quality and use for decision making at primary health care units to improve health service delivery of maternal newborn child and adolescent health, Tigray Ethiopia 2018

Abstract: Objective: information use is fundamental for evidence based decision making but data quality and information use in health facility is limited in low and middle income countries. Therefore, a facility based cross sectional using mixed approach was conducted to assess data quality and use for decision making in 12 selected health facilities of Tigray, Ethiopia, 2018. Results: District Health Information System 2 (DHIS2) software was practiced in 12 of the facilities. Completeness and consistency rate of regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Generally, the study findings indicate that the quality of data collected manually in paper based and reported in HIS was poor as compared to the data collected directly using the current electronic system. These findings support evidence from previous observations which showed that the quality of HIS data gathering and reporting was poor in low and middle income countries (Assefa Ayalew et al, 2020;Begum et al, 2020;Manya & Nielsen, 2016;Ouedraogo et al, 2019) when using the paper system as compared to using the electronic system. Indications are that inadequate information may be available for decision-making purposes at the health facility if data are collected using paper based systems.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Generally, the study findings indicate that the quality of data collected manually in paper based and reported in HIS was poor as compared to the data collected directly using the current electronic system. These findings support evidence from previous observations which showed that the quality of HIS data gathering and reporting was poor in low and middle income countries (Assefa Ayalew et al, 2020;Begum et al, 2020;Manya & Nielsen, 2016;Ouedraogo et al, 2019) when using the paper system as compared to using the electronic system. Indications are that inadequate information may be available for decision-making purposes at the health facility if data are collected using paper based systems.…”
Section: Discussionsupporting
confidence: 90%
“…Another study reported that the completeness rate of register and reports was 53.5%, and 56.3% respectively, and the overall consistency rate was 38.9% (Assefa Ayalew et al, 2020). Furthermore, another study on antenatal care fourth visit, postnatal care, fully immunized and total malaria revealed the most inaccurate data elements (Endriyas et al, 2019).…”
Section: The Dimensions Of Data Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“… 23 24 While inadequate knowledge of RHIS is a cross-cutting issue, it proved more problematic at lower levels of the health system, where data are generated. Other studies report that not understanding indicators 25 and poor competency in recording 26 affect data quality.…”
Section: Discussionmentioning
confidence: 99%